EKSISTENSI NILAI KEARIFAN LOKAL DAN BUDAYA MASYARAKAT DESA CIPULUS DI ERA GLOBALISASI - Fovi Sriyuliawati (Jurnal Pengabdian Kepada Masyarakat, 2024)
Indonesia is one of the countries that has a diverse culture. Bhineka Tunggal Ika, which means different but still one. This motto is a description of the diversity that occurs. The existence of local culture in this era of globalization is one of the problems that must be resolved immediately. In this era of globalization, there are still several areas that still preserve and maintain intact the culture that is part of the traditional tradition. One of them is a village located in Cikijing District, Majalengka Regency, precisely in Cipulus Village. The village still preserves traditional culture. There are several traditions that are still carried out today, including Gusaran, Tilawat, and Pareresan. These three traditions have existed since ancient times. The solidarity of the community in the village is also felt to be very good. Not only adults who contribute to the implementation of the culture. Children and teenagers also contribute well. This incident is something rare, in an era of the onslaught of many western cultures that have entered and been well received in society, Cipulus Village still maintains the traditional culture that has become a habit every year